An autonomous IIoT-based monitoring systems for intelligent rock bolts in underground mines - P Hartlieb; M Varelija; M Noeger (The Australasian Institute of Mining and Metallurgy, 2024)
Rock bolts are important in underground mining as they provide support to the rock mass around the excavation. They are the most common reinforcement method in mining and civil engineering excavations. The length of the bolts, types and spacing between them can be varied, depending on the reinforcement requirements and the use case (Kolapo, Onifade and Praise, 2022). The rock bolt provides safety and stability for the rock mass in the excavation area and they can be mechanically anchored, grouted, or friction anchored. They normally don’t have a measurement option and there is a possibility that it failed without showing visible signs on the surface, especially in grouted rebar bolts where they can still have some residual strength. Therefore, support functionality can be lost without recognising it. To overcome that, sensors can be installed on all three previously mentioned bolt systems. Intelligent bolts with implemented measuring systems have a function of showing changes and indicating if there is some damage on the bolt. So, it can be said that intelligent rock bolts are regular bolts equipped with additional instruments which are helping us detect potential instabilities inside of the rock mass or malfunction of the bolt itself. Changes in rock mass can be tracked, by measuring rock bolt reaction concerning the excavation response. Rock mass damage and instabilities are therefore measured in terms of rock mass deformation. Moreover, other additional information depending on the type of the sensor device could be collected. Based on such measurements, information about rock mass state can be derived. Different rock bolt types work at different reaction principles. Therefore, limitations on sensor application and information that can be extracted must be considered.